Lesão encefálica adquirida e o processo de cuidado: a ótica dos profissionais de saúde de um hospital universitário - Möller, Camila Dias (2020)
Introduction: This research focused on the Acquired Brain Injury (ABI) from the perspective of health professionals working at a University Hospital; aimed to analyze how these professionals recognize the care process and the health needs of people with ABI they monitored during the acute phase. Method: Descriptive, exploratory and qualitative quantitative study. The sample consisted of professionals from different areas and from different sectors of the referred hospital, who receive subjects affected by ABI. The data collection was carried out between December 2019 and May 2020, through the application of a semi-structured questionnaire, specially designed for this research, which sought to characterize workers (initial letters of name, sex, age, profession, year of graduation, level of education, sector of professional activity, length of experience in the sector) and their conceptions about the necessary assistance to people with ABI, if the professional works in a team, with which professionals, how does his work team characterize, the repercussions of the work, etc. The statistical analysis was descriptive, using the Statistica 9.1 Software. Qualitative analysis was performed using the content analysis method. Results: The results are presented in two articles; the first - “Teamwork and care for subjects with ABI: conceptions and experiences of professionals at a university hospital” - whose objective was to characterize the conditions of care, analyzing the speeches through the registration units that enabled the elaboration of two categories: i) professional actions and their repercussion among people with ABI and ii) teamwork process. The second article - "Health needs of people with ABI monitored at a university hospital: the perspective of health professionals from different sectors" - whose objective was to identify the view of professionals about the health care needs of people with ABI, analyzed the emerging speeches in three categories: i) identification of care needs for people with ABI; ii) potential of assistance provided by professional teams and iii) weaknesses observed by teams from different sectors of the hospital. Conclusion: It is concluded that the health professionals dedicated to care in the acute condition of the ABI recognized that they perform their functions with technical responsibility, but the execution of teamwork is fragmented. They also recognized the need to expand their conceptions on how to exercise their practices in multidisciplinary teams with interdisciplinary and / or transdisciplinary approaches.